AYURVEDIC APPROACH IN MANAGEMENT OF AMAVATA W.S.R TO RHEUMATOID ARTHRITIS: A CASE STUDY - Puesh Pargotra, *Priya; Thakur, Bhawit (International Journal of Ayurveda and Pharma Research, 2019)
Amavata is a chronic immune-inflammatory systemic disorder mainly affecting synovial joints, caused due to formation of Ama and its association with vitiated Vata dosha and deposition in Shleshma sthana i.e., (joints). Clinical features of Amavata resembles with Rheumatoid Arthritis, it poses a challenge for the physician owing to its chronicity, morbidity and complications. The treasure of Ayurveda therapeutics has laid out detailed treatment line for Amavata. A 40years old female patient reported to our hospital with Shoola and Stambha of metacarpophalangeal joints of both hands followed by Shoola in corresponding knee joints 1 year back. This was succeeded by Shoola and mild Sotha on bilateral wrist, ankle and elbow joints. Blood investigations of the patient revealed that she was anemic with Hb-8.2g/dl, had elevated ESR-74 mm Hg fall in 1st hr, and reactive RA factor. Based on clinical examination and blood investigations, diagnosis of Amavata was made and Ayurvedic treatment protocol was advised with Baluka sweda (sudation) as external application for 21 days, Agnitundi vati before food for 7 days, Dashmoolarasnadi kashayam and Simhanad guggul after food for oral intake for 60 days. The patient was asked for follow up every 15 days up to total of 60 days. Assessment was done subjectively based on clinical symptoms and blood investigations as objective parameters. There was substantially significant improvement and the patient felt relieved from Shoola, Shotha and Stambha of the joints after the treatment. This case study reveals the potential of Ayurvedic treatment protocol in management of Amavata.